Creating connections in teaching and learning - Abawi, Lindy; Conway, Joan M.; Henderson, Robyn (Research on teaching and learning., 2011)
This book explores the wide range of contexts in which research into creating connections in learning and teaching may take place. Creating connections can encompass making links, crossing divides, forming relationships, building frameworks, and generating new knowledge. The cognitive, cultural, social, emotional and/or physical aspects of understanding, meaning-making, motivating, acting, researching, and evaluating are explored as constituent forms of creativity in relation to such connections.From this exploration the authors identify varied connective contexts and means which include the learner, the educator, the organisation, and the relevant community. The crossing of divides, forming learner-educator relationships, bringing together diverse groups of learners, establishing networks and partnerships among educators, and establishing links between organisations and communities are all considered as connections which can be created by and within the learning and teaching dynamic.By examining the factors which help to facilitate and/or restrict the possibilities for creating connections in educational contexts, implications for and outcomes of learning and/or teaching arise from the connections created. The final chapter of this book will explicate the realisations that have emerged for educators and researchers working to create connections. These offer suggestions for future directions and enunciate what and how connections might contribute to both educational institutions and the broader society.